Optimasi Parameter Operasi Mesin Pengering Kain Sistem Putar Berbasis Elemen Pemanas Menggunakan Software Minitab dengan Metode 2k Faktorial Design - Rayhan Bramantyo; Ibnu Abdul Rosid; Adinda Sekar Ludwika; Alfauzi Alfauzi (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Conventional fabric drying still depends on sunlight, making the process highly affected by weather conditions and resulting in inconsistent drying performance. This study aims to evaluate the effects of heating element temperature, drum rotational speed, and drying time on fabric moisture content and to determine the optimal operating parameters. A rotary fabric dryer equipped with an electric heating element was developed by modifying a 6 kg automatic washing machine. A two-level full factorial design was employed using three factors: heating element temperature (40°C and 50°C), drum rotational speed (280 rpm and 920 rpm), and drying time (10 and 15 minutes). Experimental data were analyzed using Minitab through analysis of variance, Pareto Chart, regression analysis, and Response Optimizer. The results showed that all three factors significantly affected fabric moisture content, with drum rotational speed having the greatest influence. The optimum condition was achieved at 50°C, 920 rpm, and 15 minutes, producing a predicted moisture content of 57.91% with a composite desirability of 0.9297. The developed dryer provides a more controlled drying process and offers improved drying efficiency for fabric applications.